The European employment strategy in an enlarged EU - Georg Fischer; Luc Tholoniat (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
This article reviews the origins, development and impact of the European Employment Strategy against the backdrop of the employment performances and policies of the EU, from the early 1990s up to the mid-term review of the Lisbon Strategy in 2005. It recalls how the issue of employment was put at the centre of the policy debate in the 1990s and of the discussion about the right balance between economic and social policy integration at EU level. While the EU-wide emphasis on employment initiated in the mid-1990s is likely to have had some positive effects, in particular in terms of a return to employment growth and an increase in participation and employment rates, many major challenges remain or have developed in the meantime. The experience of the EES shows that there is room for a European strategy to promote growth and jobs.
Keywords: 330; Beschäftigungspolitik - historische Entwicklung; Beschäftigungspolitik; politischer Entscheidungsprozess; politischer Wandel; Beschäftigungsentwicklung; Arbeitsmarktentwicklung; Produktivitätsentwicklung; Wirtschaftsentwicklung; Europäische Union